A socio-legal inquiry into management and development of awqaf in Bangladesh : challenges and prospects - Karim, Md Fazlul (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2016)
This research is an attempt to respond to the pressing needs to revive and explore the prospects of awqaf in Bangladesh that has not been seen in any published doctoral dissertations on this area in the last few decades. awqaf in Bangladesh represents a sector with huge potentials for welfare oriented developments and the benefits of unprivileged section of the population. Aligned with its specific research objectives the study seeks to explore the challenges that the waqf administration in the country is now facing. Several research hypotheses were set questioning the suitability of the Waqf Ordinance 1962, which has been thoroughly examined. These were set in order to check for any possible lacuna and loopholes that may have led to handle the administration and management of the waqf institutions inefficiently in the country in question. Relevant data were collected for the analysis of both from primary and secondary sources, and existing relevant literatures have been reviewed. This study seeks to demonstrate that despite huge potentials and prospects for welfare based developments, awqāf in Bangladesh remained largely untapped for diverse challenges consisting legal and administrative hurdles. Attempts are also made in this study to explore the extent of serious lacking in efficiency mainly in matters related to the administration and management of waqf in Bangladesh that have led waqf properties and assets to remain open to misuse and mismanagement. This includes inter alia, shortage of competent personnel to administer waqf entities, illegal occupation of waqf properties, leasing and renting of waqf properties at a lower rate, and misappropriation of waqf funds. As a result, the institution of waqf in Bangladesh faces a stagnant situation due to which many waqf properties remained underutilised or even idle generating no yield. The study argued that the present legal and regulatory framework is inadequate for the proper development of waqf, and as such an appropriate legal framework would pave the way for exploiting the fullest potentials of awqaf. This research finds that there is a pressing need to work on reforming and developing the waqf establishment in Bangladesh from legal and regulatory framework as well as the administrative set up of the waqf administration, which is expected to contribute as stepping stones for further research and stimulate future researchers to come up with innovative ideas for the developments of awqaf in Bangladesh. The research also suggests ways to resolve issues related to effective management of awqāf in Bangladesh jurisdiction. Given that, the role of awaqf in poverty alleviation and prospects for cash waqf in Bangladesh has been duly pointed out. This study provides valuable policy recommendations which are expected to be useful to the appropriate policy makers in their efforts to administer and manage these important institutions efficiently and sustainably. It also recommends ways for revitalising awaqf such as enacting a new Waqf Act, developing urban waqf, introducing waqf bond, collaborating with other Muslim countries, establishing a national waqf advisory board, educating mutawallis and providing them appropriate training, enhancing staff benefits, establishing waqf tribunal, conducting a national waqf survey, establishing a shariah board, investing waqf properties in real estate and commercial building, developing statistics/database for the family waqf, democratising and decentralising waqf administration, setting-up guidelines and legislations for managing darghas and takias, initiating cash waqf policy, developing Mosques properties, and establishing research divisions.